2022
DOI: 10.32598/sija.2021.3160.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Supplemental Health Insurance on Out-of-Pocket Payments for Elderly Households in Urban Areas of Iran: Hackman Sample Selection Model

Abstract: Objectives: Considering the growth of the elderly population and the need of the elderly for health services and the importance of supplementary insurance on improving the quality of life of the elderly households, this study aimed to investigate the effect of supplementary health insurance on out-of-pocket payments for elderly households in urban areas of Iran. Methods: this descriptive-analytical and applied study was conducted at the national level using the two-stage Hackman econometric method in Stata 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The positive effect of health insurance on higher OOP expenditures has been supported by empirical studies (11,12,13). These studies highlight several reasons for this phenomenon.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…The positive effect of health insurance on higher OOP expenditures has been supported by empirical studies (11,12,13). These studies highlight several reasons for this phenomenon.…”
Section: Resultsmentioning
confidence: 75%
“…Similarly, Shahraki and Ghaderi (2019) and Ahmadi and Taheri (2017) found that secondary insurance plans increased OOP expenditures among Iranian urban households and the overall Iranian population, respectively (12,13).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations